ANTOLOGI KITAB HADITS KARYA ABDUL RA’UF AS-SINGKILI - Ari Fauzi Rahman (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
Abdul Ra'uf as-Sinkili is a Scholars Nusantara productive on produce the various of scientific work. The book of Fiqh Tasawuf, Tafsir and hadits are from discipline science that Abd al-Ra'uf al-Sinkili had made his written. After doing safari the science to the other country Ara, specifically since 19 years Abd al-Ra'uf al-Sinkili back to his fatherland, it is Aceh. His caming to aceh has succeeded to muffle the polemic of wujuddiyah concept who has spearheaded by Hamzah al-Fansuri and Syamsudin al-sumatrani with Nurruddin ar-Raniri the Scholars Nusantara from India with his upswing (tajdid). Al-Sinkili's posisition becoming mediate scholars with compromise both of them. In view of the Nusantara condition of society of that time, there are a lot of al-sinkili posts submitted the tasawuf values. Such as on his book interpretatations Tarjuman al-mustafid which the tasafuw is also in his memoirs Syarah lathif 'ala arba'iina, Imam an-Nawawi and Mawaiz al-Badi'ah hadiths. With a tasawuf feature that the Nusantara's public prefers to that time to force clerics to teach distorted islamic teachings to make them easy to accept by the community. The arrival of al-Sinkili to Aceh's sutanate brought the doctrine with renewal movement but not as these Al-Raniri's thaught that bringing about the islamic conflict until heresy againts fellow muslims. Even in the end, al-Sinkili on his works criticizes the teachings of Hamzah al-Fansuri, Syamsuddin al-Sumatrani with the teachings of his wujudiyah and Nurrudin -Raniri with his renewal movement.